Acoustic Analysis of Hoarseness - Nataraja NP (Journal of All India Institute of Speech and Hearing, 1970)
'Hoarseness' is a general term used  by Speech Clinicians and others to describe a variety of perceived voice abnormalities. Hoarseness has been identified as  a  symptom of abnormal laryngeal condition. Considerable  emphasis has been placed on this symptom. Several  approaches, including acoustic, cinematographic,  aerodynamic and electrophysiological have been utilised to explore the mechanism and pathologic physiology of hoarse voice production. However, the evaluation of hoarseness, the estimation of degree and quality of hoarseness has been made chiefly on the basis of clinicians' subjective perception. This practice has led to the creation of confusing terms to describe similar changes of vocal quality. Terms like harsh, husky, raspy, breathy and  strindent are also often used  by  clinicians' hoarseness. Little is known  about acoustical properties of variations of pathologic voices and related dysfunction of the larynx.